Formulation, characterization and Evaluation of Transdermal Film Containing Naproxen - Y.Phalguna,; Ch.Shivalumar,; N.Suresh,; B.Mahender,; Ch.Prakasham, (IJPAR JOURNAL, 2013)
Transdermal drug delivery system has numerous advantages over the more traditional drug delivery systems. This includes high bioavailability, steady drug plasma concentration, absence of first pass hepatic metabolism effect. Transdermal film is an adhesive film that has a coating of a drug that is placed on the skin to deliver a specific dose of the drug into the bloodstream over a period. The aim of present study an attempt was made to design the transdermal drug delivery system of naproxen with Ethyl Cellulose polymer in various concentrations. Transdermal films were prepared by solvent casting method by using Dibutylpthalate as plasticizer. The prepared films were characterized in physical appearance, thickness, drug content, weightvaration, Folding endurance, percentage moisture uptake and in-vitro release study.